2007
DOI: 10.2514/1.26824
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Tube Banks in Crossflow Using Entropy Generation Minimization Method

Abstract: An entropy generation minimization method is applied as a unique measure to study the thermodynamic losses caused by heat transfer and pressure drop for a fluid in cross flow with tube banks. The use of entropy generation minimization allows the combined effect of heat transfer and pressure drop to be assessed through simultaneous interaction with the tube bank. A general dimensionless expression for the entropy generation rate is obtained by considering a control volume around a tube bank and applying conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 23 publications
(10 reference statements)
0
4
0
1
Order By: Relevance
“…Такая оптимизация возможна только с применением термодинамического анализа методом минимизации производства энтропии. Работы [12][13][14] принадлежат группе исследователей лаборатории микроэлектро-ники Университета Ватерлоо (Канада). В работах рассмотрена оптимизация компактных оребренных микроканальных охладителей методом минимиза-ции производства энтропии.…”
Section: анализ литературных данных и постановка проблемыunclassified
“…Такая оптимизация возможна только с применением термодинамического анализа методом минимизации производства энтропии. Работы [12][13][14] принадлежат группе исследователей лаборатории микроэлектро-ники Университета Ватерлоо (Канада). В работах рассмотрена оптимизация компактных оребренных микроканальных охладителей методом минимиза-ции производства энтропии.…”
Section: анализ литературных данных и постановка проблемыunclassified
“…Minimization of entropy generation as a design tool to determine best device geometry and operation, especially for heat exchangers, has been established for macro-scale configurations (see Bejan 1996Bejan , 2002Sahin 1998Sahin , 2000Mahmud & Fraser 2003;Mansour et al 2006;Khan et al 2007;Ko & Wu 2009; among others). However, fluid flow in microchannels exhibits dominant features often non-existing or less influential in macrochannels, e.g., wall-slip velocities for some gases, entrance effects because of the short conduit length, significant surface roughness in relation to microchannel height (or hydraulic diameter), etc.…”
Section: Liquid Flow In a Microchannelmentioning
confidence: 99%
“…The question here is, can the tubes in shell be oriented such that the heat transfer between the two fluids is enhanced, while the pressure drop across the heat exchanger is still reasonable. Tube arrangement optimization in shell-tube heat exchangers has been studied extensively by employing various methods [7][8][9][10][11][12][13]. These investigators have shown that the spacing, orientation, and the arrangement of tubes in the shell have profound influence on the thermal performance.…”
Section: Introductionmentioning
confidence: 99%